1993
DOI: 10.1007/bf03162537
|View full text |Cite
|
Sign up to set email alerts
|

High-pressure EPR studies of intermolecular interactions in solids

Abstract: High-pressure technique as applied to studies of different problems in solid state physics by EPR spectroscopy is presented. An influence of hydrostatic pressure up to 500 MPa on a weak superexchange coupling between Cu(II) ions in monome¡ and dimeric copper(II) compounds is described. Both decrease and increase in the eoupling is observed under pressure depending on the crystal and molecular structure but in all cases a dominant contribution is due to a shortening of intermolecular distances, whereas molecula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 70 publications
(49 reference statements)
0
7
0
Order By: Relevance
“…For effective pore widths of 5.17 Å, as the temperature increased, the selectivity of CHClF 2 gradually decreased from 4.63 to 4.59 to 4.53. These results can be ascribed to the fact that intermolecular interactions in the gas framework are only weakly dependent on temperature. , …”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…For effective pore widths of 5.17 Å, as the temperature increased, the selectivity of CHClF 2 gradually decreased from 4.63 to 4.59 to 4.53. These results can be ascribed to the fact that intermolecular interactions in the gas framework are only weakly dependent on temperature. , …”
Section: Resultsmentioning
confidence: 94%
“…These results can be ascribed to the fact that intermolecular interactions in the gas framework are only weakly dependent on temperature. 44,45 Next, breakthrough experiments at various total pressures (0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, and 1.0 MPa) were performed to observe the actual selectivity for CHClF 2 over CHF 3 in a nanoporous carbon material. For convenient comparison with simulation results, the majority of the effective pore widths in the carbon PK1 sample employed are in the range of 5.17−8.30 Å (H = 8.52−11.65 Å).…”
Section: Industrial and Engineering Chemistry Researchmentioning
confidence: 99%
“…The above theories are used in description of motional averaging effects in hyperfine structure of free radicals with isotropic g-factor. We have generalized this description for the case of different g-factors [18,19]. This is essential in description of exchange averaging effects for Cu 2+ displaying strong g-factor anisotropy.…”
Section: Temperature Dependence Of the Spin-hamiltonian Parametersmentioning
confidence: 94%
“…Also the piridinium hydrogen (see NH groups in figure 1 EPR experiments under normal pressure were performed on a Bruker ESP380E spectrometer operating in CW mode at frequency 9.4-9.8 GHz over the temperature range 4.2-300 K using an Oxford CF-935 flowing helium cryostat. High pressure EPR measurements at various temperatures were performed on a Radiopan SE/X-2547 spectrometer with hydrostatic pressure up to 400 MPa using a high pressure chamber and corrundum TE 112 resonator described previously [8].…”
Section: Methodsmentioning
confidence: 99%
“…In the vast majority of weakly coupled systems the exchange integral was found to be strongly temperature dependent in contradiction to the strongly coupled dimers. Temperature [7] and pressure [8] EPR experiments have shown that the main reason for the temperature variations of J is thermal lattice contraction affecting intermolecular bonds. The problem is complicated by the fact that often a few exchange pathways interfere and various molecular groups such as SO 4 , NO 2 and NH 2 involved in a hydrogen bond system have different efficiency for the superexchange transmission.…”
Section: Introductionmentioning
confidence: 99%